Avaliação do Efeito de Atributos Intrínsecos e Extrínsecos na Formação de Valor pelo Cliente: o caso do mercado de touros certificados da raça Nelore - Silveira, Vitor Cardoso da (2022)
Agribusiness is currently responsible for approximately 26.6% of the Brazilian GDP, with growth expected. In recent years, the country has always been among the first places in terms of production and exports in various agribusiness production chains (among them: soy, beef, chicken, corn, sugarcane, coffee and cotton). Livestock farming reached in the year 2020 a percentage close to 10% of the national GDP and inserted in this is the object of study of this research: the certified Nelore bull sold via auction. Supported by a theoretical basis that involves constructs related to competitive advantage, concepts and value classifications, choice attributes (intrinsic and extrinsic) and organizational buying behavior, the main objective of this thesis was to evaluate the effect produced by attributes intrinsic and extrinsic factors in the formation of value by the customer. It is argued that the customer's purchase behavior and the formation of the final price of the auctioned animal is a function not only of intrinsic attributes related to the breeding bull, but that extrinsic attributes related to the auction event, brands and certifications are also part of this composition. The methodological approach of the research is a mixed one, involving quantitative and qualitative study. In the quantitative study, data were collected through auction catalogs and also through recordings of events, using the multivariate technique of simple and multiple linear regression data for analysis. In the qualitative study, data were extracted through interviews with active auction participants, who were buyers, sellers and auctioneers, as well as information obtained through recordings of the events. The results of the study indicate that approximately 73% of the final exchange value of the auctioned certified Nelore bull is explained by intrinsic attributes present in the event catalogs (animal weight, age in months, scrotal circumference, MGTe and EPDs) and extrinsic attributes related to the auction (initial price, number of proposed bids and lot size), adding that the extrinsic attributes related to the auction are more representative in the formation of value by the customer than the intrinsic attributes analyzed. It is also added some research findings found through the qualitative study, theoretically, the organizational buying behavior is not strictly rational, as advocated by the current theory, but is also influenced by visual and emotional variables and, empirically, it is understood that bull buyers at auctions have very different profiles ranging from the most technical to the most visual, which is a factor of strong influence on buying behavior, understanding that the perception of value of this individual, considering intrinsic and extrinsic choice attributes, is divergent. Finally, there are significantly positive influences on the final price of the animal, pointed out by the present research: total economic genetic merit, expected differences in progeny, genealogy, auction attributes, visual attributes and event brands. Keywords: Nelore bull; Choice attributes; Exchange value; Auction; organizational buying behavior.